Observing international relations : Niklas Luhmann and world politics - Albert, Mathias; Hilkermeier, Lena, 1971- (London ; New York : Routledge, 2004)
Observing International Relations draws upon the modern systems theory of society, as developed by Niklas Luhmann, to provide new perspectives on central aspects of contemporary world society.
Introduction / Mathias Albert -- On the modern systems theory of society and IR. Contacts and disjunctures between different kinds of theorizing / Mathias Albert -- Politics, modern systems theory and the critical purpose of international relations theory / Thomas Diez -- "Corpus mysticum": Niklas Luhmann's evocation of world society /Stefan Rossbach -- The "English school" and world society / Chris Brown -- Sociological institutionalism and the empirical study of world society / George M. Thomas -- World society from the bottom up / Lothar Brock -- World society, systems theory and the classical sociology of modernity / Dietrich Jung -- Systems and sovereignty -- a systems theoretical look at the transformation of sovereignty / Anders Esmark -- "World opinion" and the turn to post-sovereign international governance / Hans-Martin Jaeger -- Society's war: the evolution of a self-referential military system / Gorm Harste -- Organizations in/and world society: a theoretical prolegomenon / Mathias Albert and Lena Hilkermeier -- Governance in a world society: the perspective of systems theory / Dieter Kerwer -- Constructivism and international relations: an analysis of Luhmann's conceptualization of power / Stefano Guzzini -- Concluding remarks / Mathias Albert.
Includes bibliographical references (pages 226-251) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Luhmann, Niklas; Luhmann, Niklas -- 1927-1998; Luhmann, Niklas, -- 1927-1998.; Luhmann, Niklas; International relations -- Social aspects; Relations internationales -- Aspect social; POLITICAL SCIENCE -- Globalization; International relations -- Social aspects; Weltpolitik; Weltgesellschaft; Systemtheorie; Internationale Politik; Relations internationales -- Sociologie